Ultrasonographic findings in long COVID: A cross-sectional study of 312 patients - Imamura, Marta; Uchyiama, Sabrina Saemy Tome; Naves, Gabriella Souza; Abicalaf, Cláudia Andréia Rabay Pimentel; Mirisola, Aline Rossetti; Santos, Artur César Aquino dos; Battistella, Linamara Rizzo; , HCFMUSP COVID-19 Study Group (Frontiers in Medicine, 2023)
Background Fatigue and muscle weakness are common complaints in COVID-19 survivors. However, little is still known about the skeletal muscle qualitative and quantitative characteristics after hospitalization due to moderate and severe COVID-19. Objectives To assess rectus femoris and vastus intermedius muscle thickness (MT) and rectus femoris echo intensity (EI) and to establish its association with demographic, clinical, functional, and inflammatory parameters in long COVID patients after hospital discharge. Methods Cross-sectional study with 312 COVID-19 patients (53.53% male; age: 54.59 ± 13.50 years), with a laboratory-confirmed diagnosis of COVID-19. Patients were assessed 3–11 months after hospital discharge. We evaluated MT of the right rectus femoris and vastus intermedius and EI of the right rectus femoris using a portable ultrasound system, 6–13 MHz, broadband linear transducer. We corrected EI using the subcutaneous fat thickness. Ultrasonographic parameters were tested in association with demographic (sex and age); functional (Handgrip strength measurement, Timed Up and Go, 1 min Sit-to-Stand test, EuroQoL-5 Dimensions-5 Levels, World Health Organization Disability Assessment Schedule (WHODAS 2.0), Post-COVID-19 Functional Status, Functional Assessment of Chronic Illness Therapy—Fatigue (FACIT), Medical Research Council (MRC) sum score, Borg Dyspnea Scale, MRC Dyspnea score, Visual Analogue Scale (VAS), Epworth Sleepiness Scale, Insomnia Severity Index, Functional Independence Measurement (FIM), and Functional Oral Intake Scale); clinical (length of hospital stay, intubation, and presence of comorbidities such as systemic hypertension, diabetes, obesity, chronic obstructive pulmonary disease, asthma), and inflammatory data assessed by the C-reactive protein and D-dimer serum concentrations. Results Rectus femoris MT was associated with age, handgrip strength, Epworth Sleepiness Scale, and subcutaneous fat thickness (r2 = 27.51%; p < 0.0001). Vastus intermedius MT was associated with age, pain intensity, handgrip strength, Epworth Sleepiness scale, FIM, and time since hospital discharge (r2 = 21.12%; p < 0.0001). Rectus femoris EI was significantly associated with the male sex, TUG, Epworth Sleepiness Scale, and C-Reactive Protein levels (r2 = 44.39%; p < 0.0001). Mean MT of rectus femoris and vastus intermedius are significantly different (p < 0.001). Conclusion After hospital discharge, long COVID patients present qualitative and quantitative skeletal muscle characteristics associated with a combination of demographic, clinical, and functional parameters.